2021
DOI: 10.1021/acs.estlett.1c00221
|View full text |Cite
|
Sign up to set email alerts
|

Forest Fires Enhance the Emission and Transport of Persistent Organic Pollutants and Polycyclic Aromatic Hydrocarbons from the Central Himalaya to the Tibetan Plateau

Abstract: Forest fires are considered one of the drivers of global carbon and aerosol emissions; however, few studies have focused on the release of persistent organic pollutants (POPs) and polycyclic aromatic hydrocarbons (PAHs) from forest fires and their regional impacts. In this study, we estimated the emissions of POPs and PAHs from South Asian forest fires and simulated the atmospheric transport of these fire-emitted pollutants to the Tibetan plateau over the Himalaya. It was found that forest fires on the souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This estimated BB contribution value was close to the 15% contribution value of incineration sources to PAH emissions in Kolkata, India, comparable with the BB contribution to PAHs (11%) at a regional background site in East China and vegetation fires to the exposure of PCDDs (1–10%) and PAHs (>10%) in Africa observed by satellite and models . However, it was higher than the estimated BB contribution (6%) of PCBs in a non-metropolitan city of northern India and lower than the contribution of forest fires on the southern slopes of central Himalaya to the atmospheric DDTs and PAHs (20–30%) during non-monsoon season . Other identified factors for PCBs are described in Section S4 of Supporting Information.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This estimated BB contribution value was close to the 15% contribution value of incineration sources to PAH emissions in Kolkata, India, comparable with the BB contribution to PAHs (11%) at a regional background site in East China and vegetation fires to the exposure of PCDDs (1–10%) and PAHs (>10%) in Africa observed by satellite and models . However, it was higher than the estimated BB contribution (6%) of PCBs in a non-metropolitan city of northern India and lower than the contribution of forest fires on the southern slopes of central Himalaya to the atmospheric DDTs and PAHs (20–30%) during non-monsoon season . Other identified factors for PCBs are described in Section S4 of Supporting Information.…”
Section: Resultssupporting
confidence: 77%
“…Many POPs have been reported in open-field BB. ,, The concentrations of PCDD/Fs and polybrominated diphenyl ethers (PBDEs) at farm sites were elevated by 6–21 times by rice straw open burning. , Emission factors of 2.6 μg/kg for ∑ 13 PCBs and 0.8 μg/kg for dichlorodiphenyltrichloroethane congeners (DDTs) were reported from subtropical eucalypt forest fires . Moreover, elevated concentrations of polycyclic aromatic hydrocarbons (PAHs), PCBs, and pesticides were found to originate from trans-Pacific and regional BB aerosol undergoing long-range atmospheric transport. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions have high proximity to the densely populated areas (mainly the Indo-Gangetic plain) of the western to eastern Himalaya (Figure S6). The previous studies based on ground-based and remote sensing-based measures also found a significant association between forest fire episodes and declining air quality over the western Himalayan region [40][41][42], the central Himalaya (Nepal) [79,80], and the eastern Himalaya [81].…”
Section: Discussionmentioning
confidence: 77%